Application of Juritraductology to Translate Legal Terms Determining a Person’s Age. The Polish-French Example - Marta Sobieszewska (Facta Simonidis)
The aim of this article is to apply the juritraductological method to the translation of age-defining terms, using Polish and French examples (‘małoletni’/‘mineur’). Juritraductology is a new field of interdisciplinary research that has been developing in France since the late 20th century. Its importance and scope are growing with the progress of work conducted by a team of researchers led by Prof. Sylvie Monjean-Decaudin at the Centre de Recherche Interdisciplinaire en Juritraductologie (Cerije) in Paris. The juritraductological method, as applied in this paper, is a three-stage translation process. The first stage, called “semasiological” (from words to concepts), allows for answering the question, “what does a word mean?” The second stage consists of a contrastive analysis of Polish and French law (comparative law). The third and last stage is “onomasiological” (from concepts to words) and answers the question “what are these concepts called?” Both approaches – onomasiological and semasiological – can be considered complementary, as they enable the implementation of mutually reinforcing tasks. The research results obtained will allow for assessment of the contribution of the new scientific discipline toward improving the quality of legal translations.